Answer:
1
Step-by-step explanation:
2x + 1 = -3x + 6
add 3x
5x + 1 = 6
subtract 1
5x=5
Divide by 5
x=1
If this is correct, please mark brainliest!
<em>3</em><em>9</em><em>></em><em>3</em><em>8</em>
<em>1</em><em>6</em><em>=</em><em>1</em><em>6</em>
<em>1</em><em>1</em><em><</em><em>3</em><em>1</em><em>5</em>
<em>5</em><em>></em><em>4</em>
<em>Hope </em><em>this </em><em>helps </em><em>you </em><em>mate </em>
<em>~♥~</em><em>♪☆\(^0^\) ♪(/^-^)/☆</em><em>♪☆\(^0^\) ♪(/^-^)/☆</em><em>♪\(*^▽^*)/\(*^▽^*)/</em><em>♪☆\(^0^\) ♪(/^-^)/☆</em><em>♪ ♬ ヾ(´︶`♡)ノ ♬ ♪</em>
A is true, b is true, but c d aren’t and e is
Answer:
huh
Step-by-step explanation: